2020
DOI: 10.1002/ejhf.1708
|View full text |Cite
|
Sign up to set email alerts
|

Use of sodium–glucose co‐transporter‐2 inhibitors in patients with and without type 2 diabetes: implications for incident and prevalent heart failure

Abstract: Type 2 diabetes (T2D) is associated with an increased risk of heart failure (HF), with recent reports indicating that HF with preserved ejection fraction (HFpEF) may be more common than HF with reduced ejection fraction (HFrEF) in patients with T2D. T2D and HF result in worse outcomes than either disease alone. Sodium–glucose co‐transporter‐2 inhibitors (SGLT‐2is) have significantly improved HF outcomes in patients with T2D and may represent a new therapeutic alternative for patients with T2D at risk for or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 106 publications
(371 reference statements)
0
36
0
2
Order By: Relevance
“…improvement in haemodynamic status, direct metabolic or vascular effects). 39 The favourable haemodynamic effects are mediated by a number of mechanisms including osmotic diuresis, natriuresis and plasma and interstitial fluid volume reduction, leading to a reduction in ventricular preload and afterload. 23,40,41 Furthermore, a mathematical model has been used, coupled with clinical data on water an electrolyte excretion, to illustrate that, unlike diuretics, SGLT2 inhibitors seem to exert a greater reduction in interstitial fluid compared with plasma volume (mediated by peripheral sequestration of osmotically inactive sodium), which may prevent plasma volume depletion and subsequent hypoperfusion occasionally observed with diuretics.…”
Section: Biological Mechanisms and Effects Of Sodium-glucose Co-transmentioning
confidence: 99%
See 1 more Smart Citation
“…improvement in haemodynamic status, direct metabolic or vascular effects). 39 The favourable haemodynamic effects are mediated by a number of mechanisms including osmotic diuresis, natriuresis and plasma and interstitial fluid volume reduction, leading to a reduction in ventricular preload and afterload. 23,40,41 Furthermore, a mathematical model has been used, coupled with clinical data on water an electrolyte excretion, to illustrate that, unlike diuretics, SGLT2 inhibitors seem to exert a greater reduction in interstitial fluid compared with plasma volume (mediated by peripheral sequestration of osmotically inactive sodium), which may prevent plasma volume depletion and subsequent hypoperfusion occasionally observed with diuretics.…”
Section: Biological Mechanisms and Effects Of Sodium-glucose Co-transmentioning
confidence: 99%
“…These favourable metabolic and reno‐protective effects may provide long‐term benefits for outcomes; however, a relatively early separation of treatment curves for worsening HF or cardiovascular mortality seen in DAPA‐HF suggests that more rapid mechanisms may be involved (e.g. improvement in haemodynamic status, direct metabolic or vascular effects) 39 …”
Section: Biological Mechanisms and Effects Of Sodium–glucose Co‐transmentioning
confidence: 99%
“…Furthermore, results from the DAPA HF trial (Dapagliflozin in Patients with Heart Failure and Reduced Ejection Fraction) and EMPEROR‐Reduced (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Reduced Ejection Fraction) showed that the risk of worsening HF or cardiovascular mortality was significantly lower with SGLT2 inhibitors compared with placebo by 25%, regardless of the presence or absence of T2DM, indicating that the therapeutic role of SGLT2 inhibitors in HF with reduced ejection fraction (HFrEF) extends to patients beyond T2DM 10–12 . Independent of their glucose‐lowering action, SGLT2 inhibitors exert broader multi‐system metabolic benefits, including reduction in cardiac inflammation and fibrosis, weight loss, reduction in blood pressure and improvement in kidney function 13,14 . These effects may contribute to improving HFpEF outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a key risk factor for the development and progression of HF [32]. The recent CARMELINA trial (Cardiovascular and Renal Microvascular Outcome Study with Linagliptin) showed that a substantially higher risk of HF hospitalization was observed in patients with estimated glomerular filtration rate (eGFR) < 60 mL/min per 1.73 m 2 compared with those with eGFR > 60 mL/min per 1.73 m 2 [33].…”
Section: Sglt-2 Inhibitors and Kidney Functionmentioning
confidence: 99%